Economic Value Added (EVA) and Market Value Added (MVA) Implications on Stock Returns - Ida Bagus Gede Udiyana; Ni Nyoman Seri Astini; I Nyoman Parta; Ni Ketut Laswitarni; Luh Asti Wahyuni (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
This study aims to examine the influence of Economic Value Added (EVA) and Market Value added (MVA) on stock returns in construction sector companies incorporated in index Lq45 period 2015-2019. The population of this study is 45 companies incorporated in the Lq45 index on the Indonesia Stock Exchange (IDX). Based on the sample selection criteria, it was obtained 3 companies entered the criteria using the purposive sampling method. The analytical techniques used in this study were multiple linear regression analyses using SPSS version 22. The results of the study showed that the Test result F indicates that the independent variables of Economic Value added (EVA) and Market Value added (MVA) simultaneously have a significant effect on the return of shares. T-test result indicates that the Market value added (MVA) variable has a significant effect on the return of the stock, while the Economic Value added (EVA) variable has no significant effect on stock returns.